2018
DOI: 10.1039/c8nj00553b
|View full text |Cite
|
Sign up to set email alerts
|

Sigma-hole interactions in the molecular and crystal structures of N-boryl benzo-2,1,3-selenadiazoles

Abstract: Crystallography and DFT reveal competition between chalcogen bonding and other intermolecular interactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 55 publications
0
19
0
Order By: Relevance
“…In each of 37 [82], 38 [83], shown in Fig. 7a, and 39 [82], the familiar four-membered {SeN … }2 synthon noted in the previous section (3.2) sustains the two-molecule aggregate, despite the presence of substituents on the non-participating nitrogen atoms; the molecule in 39 has mirror symmetry encompassing the fused-ring system. The molecules in 40 [84] and 41 [85] feature pyridyl-nitrogen atoms in the six-membered ring fused to the selenadiazole ring.…”
Section: Two-molecule Aggregates Featuring Two Se … N Interactions: Selenadiazole Ringsmentioning
confidence: 88%
See 1 more Smart Citation
“…In each of 37 [82], 38 [83], shown in Fig. 7a, and 39 [82], the familiar four-membered {SeN … }2 synthon noted in the previous section (3.2) sustains the two-molecule aggregate, despite the presence of substituents on the non-participating nitrogen atoms; the molecule in 39 has mirror symmetry encompassing the fused-ring system. The molecules in 40 [84] and 41 [85] feature pyridyl-nitrogen atoms in the six-membered ring fused to the selenadiazole ring.…”
Section: Two-molecule Aggregates Featuring Two Se … N Interactions: Selenadiazole Ringsmentioning
confidence: 88%
“…In 39 [82], where the fused-ring system is located on a mirror plane, and 48 [91], the aggregate has 2-fold symmetry. In the crystal of 41 [85], two independent molecules comprise the asymmetric-unit and one of these self-associates about a centre of inversion to form the aggregate.…”
Section: Two-molecule Aggregates Featuring Two Se … N Interactions: Selenadiazole Ringsmentioning
confidence: 99%
“…Dimeric benzoselenadiazoles, and benzotelluradiazoles have been well-studied. [7][8][9][10] It has been found that the strongest chalcogen-bonding interactions are at least as strong as the conventional H-bonds, but unlike H-bonds, they are surprisingly not solvent dependent. [11] Te forms the strongest chalcogen bonding interactions compared to the other chalcogens, which can reach up to 7 kcal/mol.…”
Section: Introductionmentioning
confidence: 99%
“…Typically, chalcogen bonding occurs between the electron deficient Group VI elements (S, Se, Te) and nucleophile sites i. e., electron donor species. Dimeric benzoselenadiazoles, and benzotelluradiazoles have been well‐studied . It has been found that the strongest chalcogen‐bonding interactions are at least as strong as the conventional H‐bonds, but unlike H‐bonds, they are surprisingly not solvent dependent .…”
Section: Introductionmentioning
confidence: 99%
“…The pnicogen bond is a case in point. It has been reasonably widely examined [34,[61][62][63][64][65][66][67][68][69][70][71][72][73][74], but little has been determined in terms of competing configurations of a given pair of molecules. For example, the complexes PH 2 R•••BrCl (R = H, F, OH, OCH 3 , CH 3 ) were studied at the MP2 level [74], focusing on two possible σ-hole arrangements: halogen-bonded vs pnicogen-bonded.…”
Section: Introductionmentioning
confidence: 99%